From interpretation to identification: a history of facial images in the sciences of emotion. - Watson, John McClain (History of the Human Sciences, 2004)
The writer indicates that shifts in the objectives and assumptions motivating the employment of images of faces in the scientific study of emotion have occurred according to the various fields and research programs within which they have been put to use, is presented. He traces these shifts through the fields of the social psychology of interwar America, 1970s cross-cultural research, and the present day neurosciences of emotion to evaluate the recent utilization of facial images as a means of associating particular emotions with particular locations in the brain.